Cross-Cultural Affective Neuroscience - Özkarar-Gradwohl, F. Gökçe (Frontiers in Psychology, 2019)
Abstract Panksepp, the father of Affective Neuroscience, dedicated his life to demonstrate that foundations of mental life and consciousness lay in the archaic layers of the brain. He had an evolutionary perspective emphasizing that the subcortical affective systems come prior to cortical cognitive systems. Based on his life-long work, the Affective Neuroscience Personality Scales (ANPS) was constructed and a new neurodevelopmental approach to personality was started. The new approach suggested that personality was formed based on the strentghs and/or weaknesses found in the subcortical basic affective systems, which are initially regulated by the mother-infant attachment styles and later by early life experiences. ANPS measured six basic affects: CARE, PLAY, SEEK, SADNESS, FEAR, ANGER; along with a Spirituality subscale. Up to date, it has been translated to several languages and these studies confirmed that ANPS is a reliable and valid tool. Based on the observation that these ANPS studies have both universal and culturally specific findings, Cross-cultural Affective Neuroscience (CAN) was initiated in 2012, with the approval of Panksepp. As a new research field, CAN aims to investigate the influence of culture on the regulation of basic affective systems. CAN claims that this influence can be studied by observing the cultural variations in (a) the level of emotional interdependency, (b) the types of reinforced or supressed affects, and (c) the types of affects that accompany interdependent or independent self-construals. Cross-cultural comparisons of Turkish and American ANPS findings and the results of our first Euro-Asian CAN project among Japan, Turkey and Germany support these claims. These cultures regulate the basic affective systems in unique ways, while maintaining certain similarities with eachother. In a way, each culture has a unique affective personality profile and a specific function in the affective network of the Global Mind. The conclusion of this review shares guidelines, suggestions and ethical codes for future CAN researches. Keywords: Panksepp, basic affects, affective neuroscience personality scales, cross-cultural affective neuroscience, big five, culture, self-construals, interdependency, independency.